Facile synthesis of Fe, Co bimetal embedded nanoporous carbon polyhedron composites for an efficient oxygen evolution reaction - Jia, Huixian; Zhang, Minzhe; Meng, Tianjiao; An, Siying; Wang, Huan; Yang, Xinjian; Zhang, Yufan (Journal of colloid and interface science, 2020)
[Display omitted] •MOFs precursors were prepared via microwave irradiation and used as self-sacrificing template.•Fe, Co bimetal embedded nanoporous carbon (Fe-Co/NPC) was prepared by a rapid and scalable strategy.•Fe-Co/NPC composites showed excellent electrochemical performance as ideal electrocatalyst for OER. The development of highly efficient, stable, and low-cost non-noble-metal electrocatalysts for oxygen evolution reactions (OER) is a major challenge for facilitate the efficiency of green energy storage. Bimetallic oxides are considered promising candidates as the electrocatalysts for OER because of their remarkable electrocatalytic activity, good stability, and low cost. In this work, ZIF-67 precursors were prepared via microwave irradiation and used as a self-sacrificing template. We proposed a rapid and scalable strategy to prepare Fe, Co bimetal embedded nanoporous carbon (Fe-Co/NPC) polyhedron composites by thermal decomposition of Fe species incorporated ZIF-67 precursor. Benefiting from the distinctive 3D polyhedron structural and compositional advantages, Fe-Co/NPC with hierarchical porous structure showed excellent electrochemical performance as ideal electrode material for OER. The resulting Fe-Co/NPC displayed outstanding electrocatalytic activity for OER with appreciable onset potential (1.59 V (vs. RHE)), small Tafel slope (53.55 mV dec−1), low over-potential (396 mV) to reach 10 mA cm−2, and excellent durability with negligible loss in current density after 1000 cycles. The current work demonstrated new insight into the design and construction of 3D structured Fe-Co/NPC polyhedron catalysts with highly electrocatalytic activity and good stability for electrocatalysis applications.